Rhythm of Borneo's paradise Sabah Malaysia - Sabah Tourism Promotion Corporation (Sabah : Sabah Tourism Promotion Corporation)
Explores the Malaysian state of Sabah, and discover its unique culture and exquisite flora and fauna
Narrator: Geoffrey Nicholson.
VHS format
Keywords: Sabah -- Description and travel